Advances in Human Aspects of Transportation Proceedings of the AHFE 2017 International Conference on Human Factors in Transportation, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA (Advances in Intelligent Systems and Computing,, 2018)
This book discusses the latest advances in research and development, design, operation and analysis of transportation systems and their complementary infrastructures. It reports on both theories and case studies on road and rail, aviation and maritime transportation. The book covers a wealth of topics, from accident analysis, vehicle intelligent control, and human-error and safety issues to next-generation transportation systems, model-based design methods, simulation and training techniques, and many more. A special emphasis is given to smart technologies and automation in transport, as well as to user-centered, ergonomic and sustainable design of transport systems. The book, which is based on the AHFE 2017 International Conference on Human Factors in Transportation, held on July 17-21, Los Angeles, California, USA, mainly addresses transportation system designers, industrial designers, human-computer interaction researchers, civil and control engineers, as well as vehicle system engineers. Moreover, it represents a timely source of information for transportation policy-makers and social scientists dealing with traffic safety, management, and sustainability issues in transport.